New Avian tracks from the lower to middle Eocene at Fossil Hill, King George Island, Antarctica - Mansilla, Héctor (2012)
Fil: Mansilla, Héctor. Instituto Antártico Chileno. Laboratorio de Palaeobiología; Chile.